1999
DOI: 10.1074/jbc.274.38.26894
|View full text |Cite
|
Sign up to set email alerts
|

Pax3 and Regulation of the Melanocyte-specific Tyrosinase-related Protein-1 Promoter

Abstract: Previous work has established that the melanocytespecific tyrosinase-related protein-1 (TRP-1) promoter is regulated positively by the microphthalmia-associated transcription factor Mitf, acting through the conserved M box and negatively by the T-box factor Tbx2, which can bind two "melanocyte-specific elements" termed the MSEu and MSEi. Both the MSEu and MSEi, which share a 6-base pair GTGTGA consensus, are also recognized by a previously unidentified melanocytespecific factor, MSF. Here we show using a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 35 publications
5
95
0
Order By: Relevance
“…Our ®ndings are consistent with the observation that USF binds to the Myc regulated E-box of the CAD gene in vivo (Boyd et al, 1998). The data do not address the molecular mechanism by which DNA binding by USF is regulated; however, several previous reports have shown that DNA binding of USF proteins is regulated by phosphorylation (Berger et al, 1998;Maekawa et al, 1991) and that the extent of phosphorylation is lower in established cell lines relative to primary cells (Galibert et al, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Our ®ndings are consistent with the observation that USF binds to the Myc regulated E-box of the CAD gene in vivo (Boyd et al, 1998). The data do not address the molecular mechanism by which DNA binding by USF is regulated; however, several previous reports have shown that DNA binding of USF proteins is regulated by phosphorylation (Berger et al, 1998;Maekawa et al, 1991) and that the extent of phosphorylation is lower in established cell lines relative to primary cells (Galibert et al, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Others such as Dhh, Msx1, Kitl, Rac1 and the markers of melanoma progression, RhoC and Timp3, were identified only in the present study. 22,23 Genes identified in other studies such as Mitf, Trp1 and Stx [13][14][15] were absent in this study. Several possible reasons exist.…”
Section: Discussionmentioning
confidence: 49%
“…Recently, it was demonstrated that Tyrp1 gene expression could be down-regulated in melanocytic cells by activation of negative regulatory factors, even in the presence of Mitf (31). Tyrp1 expression is also regulated by 2 elements, termed MSEu and MSEi, which act as negative regulatory elements (32,33). Binding of Pax3, a paired homeodomain transcription factor involved in melanocyte development, to these elements up-regulates Tyrp1 expression (32).…”
Section: Tyrp1 Its Genetic Structurementioning
confidence: 99%
“…Tyrp1 expression is also regulated by 2 elements, termed MSEu and MSEi, which act as negative regulatory elements (32,33). Binding of Pax3, a paired homeodomain transcription factor involved in melanocyte development, to these elements up-regulates Tyrp1 expression (32). The brachyury-related transcription factor, Tbx2, binds to the MSEu and MSEi elements of Tyrp1 and down-regulates Tyrp1 expression (33).…”
Section: Tyrp1 Its Genetic Structurementioning
confidence: 99%